Antithrombotic drug does not affect the positive predictive value of an immunochemical fecal occult blood test. Issue 3 (10th December 2013) - Tsuji, Yosuke; Gunji, Toshiaki; Sato, Hajime; Ono, Akiko; Ito, Takafumi; Ohata, Ken; Yamamichi, Nobutake; Fujishiro, Mitsuhiro; Matsuhashi, Nobuyuki; Koike, Kazuhiko
Abstract : Background and Aim: Antithrombotic drugs may affect the diagnostic performance of immunochemical fecal occult blood test (iFOBT) for colorectal cancer (CRC) screening. The aim of the present study was to assess the effect of antithrombotic drugs on the diagnostic performance of iFOBT. Methods: We analyzed 1016 patients who underwent colonoscopy for positive iFOBT. Patients were classified as follows: patients who had advanced neoplasms detected and those who did not; patients who had cancers detected and those who did not; patients who had any neoplasms detected and those who did not. We compared the following factors between two paired groups: sex, age, endoscopists' experience, and antithrombotic drug usage. Results: A total of 139 patients were taking antithrombotic drugs (13.7%). Advanced neoplasms, cancers, and any neoplasms were detected in 196 (19.3%), 59 (5.8%), and 490 (48.2%)patients, respectively. There were no higher detection rates in the antithrombotic drug (–) group than in the (+) group (advanced neoplasms: 19.3% vs 19.4%, P  = 1.000; cancers: 5.8% vs 5.8%, P  = 1.000; any neoplasms: 48.4% vs 47.5%, P  = 0.856). Multivariate logistic regression analysis revealed that none of aspirin, warfarin, or other antithrombotic drugs was a significant factor for advanced neoplasms (95% CI 0.350–1.216, P  = 0.179; 95% CI 0.421–1.899, P  = 0.772; 95% CI 0.323–1.810, P  = 0.764, respectively). As to cancers and any neoplasms, no antithrombotic drug also proved to be a significant factor. Conclusion: The present study demonstrated that the positive predictive value of iFOBT was not affected by ongoing antithrombotic therapy.